Combined prognostic value of malnutrition using GLIM criteria and renal insufficiency in elderly heart failure. (16th November 2021) - Oguri, Mitsutoshi; Ishii, Hideki; Yasuda, Kenichiro; Sumi, Takuya; Takahashi, Hiroshi; Murohara, Toyoaki
Abstract: Aims: We aimed to investigate the prognostic impact of malnutrition, defined by the Global Leadership Initiative on Malnutrition (GLIM) criteria, stratified by renal function in hospitalized patients with acute decompensated heart failure (HF). Methods and results: In this retrospective study, 314 patients who were hospitalized for acute decompensated HF from August 2019 to October 2020 were enrolled. We evaluated malnutrition using the GLIM criteria during the time of admission. The primary outcome was 90‐day all‐cause mortality. The median patient age was 82 years, and 90‐day mortality was 14.0%. In total, 76 (24.2%) patients were malnourished according to the GLIM criteria. Malnutrition defined by the GLIM criteria [adjusted hazard ratio (HR) 1.41, 95% confidence interval (CI) 1.02–1.91, P = 0.036] and renal insufficiency [adjusted HR 2.59, 95% CI 1.07–6.28, P = 0.035 for estimated glomerular filtration rate (eGFR) < 30 mL/min/1.73 m 2 vs. ≥60 mL/min/1.73 m 2 ] were identified as independent predictors of 90‐day mortality after adjustment for age, systolic blood pressure, and serum sodium level. In the combined setting of both variables, patients with malnutrition and eGFR < 30 mL/min/1.73 m 2 had a markedly higher risk of 90‐day mortality compared with those without malnutrition and eGFR ≥ 60 mL/min/1.73 m 2 (adjusted HR 3.92, 95% CI 1.10–13.9, P = 0.035). Adding both eGFR and malnutrition, defined by the GLIM criteria, to the baseline model with established risk factors improved both net reclassification and integrated discrimination greater than that of the baseline model (0.606, P < 0.001 and 0.050, P = 0.002, respectively), even when compared with the model with malnutrition by the GLIM alone (0.463, P = 0.002 and 0.034, P < 0.001, respectively). Conclusions: Nutrition screening using the GLIM criteria stratified by renal function could clearly predict 90‐day mortality in hospitalized patients with acute decompensated HF.